(untitled) (ENTHYMEMA, 2025)
This article introduces characterisation of the tender narrator concept by Polish writer Olga Tokarczuk, which was a central point in her Nobel Prize lecture (2019). During the identification, three key elements of Tokarczuk’s project are specified: the bond of diegetic forms with climate and environmental crisis of the Anthropocene; dynamically changing, fragmented collective and individual perspectives; and the titular narrative tenderness manifested in sensitivity to more-than-human voices, networks, and relations. Through this, the potential of this idea is included in the repertoire of econarratological research and, more broadly, non-anthropocentric narrative theories. To detail the manifestations of the fourth-person narrative, as the tender narrative is also called, this paper problematises spatiotemporal experiences based on the example of Tokarczuk’s novel The Empusium (2024). In the analysis of how representations of time and space are mediated in the tender story, aspects such as interdependencies, despatialisation and fragmentation are brought to the fore.